Effects of Community of Inquiry on EFL students’ vocabulary learning motivation in a blended learning environment - Chuane, Qiu; Xiangjun, He (Frontiers in Education, 2025)
In China, the conventional structure of classrooms frequently demotivates students’ vocabulary learning. To solve the dilemma, blended learning provides a more motivated, learner-centered, and engaged classroom. Taking the Community of Inquiry (CoI) framework and Self-Determination Theory (SDT) as the theoretical basis, this study examines the structural relationships between the three dimensions of CoI—Teaching Presence, Social Presence, and Cognitive Presence—and four types of Vocabulary Learning Motivation (VLM): Intrinsic Motivation, Identified Regulation, Introjected Regulation, and External Regulation among Chinese university students. A quantitative survey method was applied, and 12 hypotheses were tested with a sample of 400 undergraduates who have participated in a blended English course at a public university in Changsha, China. Utilizing Structural Equation Modeling (SEM) technique, results showed notable positive predictive effects of the three dimensions of CoI on the four aspects of VLM. Exceptionally, Teaching Presence did not predict significantly with Identified and Introjected Regulation. These findings highlight the potential of CoI-based blended learning to improve vocabulary acquisition by promoting diverse motivating factors. Consequently, this study enhances the theoretical application of the CoI and SDT in the EFL context. It also provides practical implications for improving blended learning environments to enhance student motivation and achievement in vocabulary learning.